Transition product design. ﻿A framework proposal for a holistic approach to systemic design - Mario Bisson; Stefania Palmieri; Alessandro Ianniello; Luca Botta (Agathón)
The Transition Design (TD) discipline is based on a design framework and methodology that prioritises social and environmental well-being and the goals of local resilience and radical changes in socio-technical contexts. Terry Irwin (2019) sees two aspects of TD as fundamental: the idea that entire societies will face a transition to sustainable futures and the realisation that this will entail changes at the systemic level. As part of the ongoing disciplinary debate, this contribution investigates the potential of new design drivers, such as territorial value and local resilience, linked to specific case studies that can be seen as best practices. The result is a theoretical framework of eight guidelines that aims to answer some of the TD process’s problems and model the requirements that can then be replicated.